Analysis Of Financial Statements In Measuring Financial Performance In Companies Listed On The Indonesia Stock Exchange (IDX) (Case Study OF PT. Kalbe Farma Tbk.) - Lilis Rakhmawati; Lia Nirawati (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study is to measure the financial performance of PT. Kalbe Farma Tbk in the period 2018 - June 2021 based on analysis of financial statements using the financial ratio method. This research was conducted at the company PT. Kalbe Farma Tbk. This research method uses quantitative desriptive. The data collection technique in this study is a documentation study. The type of data used by this study is qualitative data in the form of information about companies and quantitative data in the form of financial statements derived from the Indonesia stock exchange. As well as the data analysis technique used is financial ratio analysis. Based on the results of the analysis, the results of the liquidity ratio research in 2018 - June 2021 are good because the ratio results are above 100%. Solvency ratio is good because the ratio results below 100%. The activity ratio is still relatively good because it is above 1. And the profitability ratio is not good because it has decreased.